THE NOVEL MOBILE DEVICE APPLICATION OF CAPSTESIA AIMED TO DEFINE THE NEED FOR FLUID THERAPY - R. S. Perfiliev; Yu. V. Skripkin; A. M. Ovezov; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии, 2018)
As a rule, methods evaluating the need and volume of fluid therapy are expensive, they require relevant equipment and it is not always available in hospitals; therefore it has been proposed to use mobile devices with Capstesia software to capture the image of the arterial pressure curve from the monitor screen and to analyze it in order to determine the variability of the pulse pressure (PPV). Materials and subjects. The efficiency of defining the need for fluid therapy using Capstesia was assessed in the clinical settings. 95 integrated measurements were performed in 19 patients with septic shock, who had the catheter installed to monitor the fluid therapy for trans-pulmonary thermodilution; and the PiCCO2 monitor was used. Simultaneously, the test with the volemic load (VLT) was conducted and PPV was tested with the aid of Capstesia. Results. The analysis revealed significantly higher mean differences and ranges of levels' consistency when testing PPV by Capstesia, in which the error rate was also higher than the acceptable level and it made 56%, whereas the method of VLT had only 20% of errors and significantly smaller mean difference and ranges of consistency levels.